(untitled) (Research, Society and Development, 2022)
Red propolis is an apicultural product of high chemical complexity from the mangrove regions of the northeastern coast of Brazil. The aim of this study was to evaluate the phenolic composition of ethanolic extracts of red propolis obtained by maceration with different concentrations and extraction cycles in order to indicate the ideal conditions to maximize the extraction of phenolic compounds. Extracts with 10, 20 and 30 g.100mL-1 were obtained and the phenolic constituents (gallic, caffeic, chlorogenic, coumaric, ferulic, catechin, kaempferol, pyrocatechin, quercetin, naringenin, daidzein, formononetin and biochanin A) were identified and quantified by HPLC. The extracts showed higher concentrations of flavonoids compared to phenolic acids. Among the flavonoids, Naringenin was found in higher concentrations followed by Formononetin, two important biomarkers of red propolis. Caffeic acid was the phenolic acid present in highest concentration. High chemical complexity was observed in the extracts, with high concentrations of compounds considered bioactive. According to what was observed, it is indicated the production of the extract with 20 grams and two cycles of extraction or with 30 grams and three cycles.